Accepting higher morbidity in exchange for sacrificing fewer animals in studies developing novel infection-control strategies. (February 2020) - Busscher, Henk J.; Woudstra, Willem; van Kooten, Theo G.; Jutte, Paul; Shi, Linqi; Liu, Jianfeng; Hinrichs, Wouter L.J.; Frijlink, Hendrik W.; Shi, Rui; Liu, Jian; Parvizi, Javad; Kates, Stephen; et al.
Abstract: Preventing bacterial infections from becoming the leading cause of death by the year 2050 requires the development of novel, infection-control strategies, building heavily on biomaterials science, including nanotechnology. Pre-clinical (animal) studies are indispensable for this development. Often, animal infection outcomes bear little relation to human clinical outcome. Here, we review conclusions from pathogen-inoculum dose-finding pilot studies for evaluation of novel infection-control strategies in murine models. Pathogen-inoculum doses are generally preferred that produce the largest differences in quantitative infection outcome parameters between a control and an experimental group, without death or termination of animals due to having reached an inhumane end-point during the study. However, animal death may represent a better end-point for evaluation than large differences in outcome parameters or number of days over which infection persists. The clinical relevance of lower pre-clinical outcomes, such as bioluminescence, colony forming units (CFUs) retrieved or more rapid clearance of infection is unknown, as most animals cure infection without intervention, depending on pathogen-species and pathogen-inoculum dose administered. In human clinical practice, patients suffering from infection present to hospital emergency wards, frequently in life-threatening conditions. Animal infection-models should therefore use prevention of death and recurrence of infection as primary efficacy targets to be addressed by novel strategies. To compensate for increased animal morbidity and mortality, animal experiments should solely be conducted for pre-clinical proof of principle and safety. With the advent of sophisticated in vitro models, we advocate limiting use of animal models when exploring pathogenesis or infection mechanisms. Graphical abstract: Image 1 Highlights: Animal experiments are indispensable proof-of-principle evaluation of new, infection-control strategies. Morbidity and mortality must be mimicked in animal infection models in order to better predict human clinical outcome. Prevention of death and recurrence must be primary efficacy targets in animal infection models. Secondary efficacy targets indirectly relevant for infection-control must not be pursued at the expense of animal lives. Exploring mechanisms of action for infection-control strategies must only be done in vitro, but not in animal models.